Physiological responses of customized probiotic fed marron, Cherax cainii (Austin, 2002) - Ambas, Irfan (Curtin University, 2015)
The use of chemotherapeutants for disease control in aquaculture is not sustainable, thus the use of probiotics in aquaculture has gained popularity. Six strains of probiotic candidates were screened and assessed for their efficiency in marron culture. Bacillus mycoides, with its antagonism ability towards pathogenic bacteria of crayfish Vibrio mimicus and V. cholerae non-01 was selected after validating it in a series of laboratory based and commercial scale feeding trials.